2014
DOI: 10.1039/c4cp00453a
|View full text |Cite
|
Sign up to set email alerts
|

Development and understanding of cobaloxime activity through electrochemical molecular catalyst screening

Abstract: Electrochemical molecular catalyst screening (EMoCS) has been developed. This technique allows fast analysis and identification of homogeneous catalytic species through tandem catalyst assembly and electrochemistry. EMoCS has been used to study molecular proton reduction catalysts made from earth abundant materials to improve their viability for water splitting systems. The efficacy of EMoCS is proven through investigation of cobaloxime proton reduction activity with respect to the axial ligand in aqueous solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
131
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 93 publications
(142 citation statements)
references
References 65 publications
11
131
0
Order By: Relevance
“…S26 and 27 † ). The inability of these sterically hindered substituted pyridines to coordinate was also observed for the [Co(dmgH) 2 (H 2 O) 2 ] system, 39 and indicated that the change(s) observed in the cyclic voltammogram of complex 1 in the presence of pyridine is not the result of Brønsted acid–base behaviour. On the other hand, the addition of 4-aminopyridine resulted in similar changes to what was observed with the addition of pyridine and further validates the use of cyclic voltammetry to assess the coordination of pyridine.…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…S26 and 27 † ). The inability of these sterically hindered substituted pyridines to coordinate was also observed for the [Co(dmgH) 2 (H 2 O) 2 ] system, 39 and indicated that the change(s) observed in the cyclic voltammogram of complex 1 in the presence of pyridine is not the result of Brønsted acid–base behaviour. On the other hand, the addition of 4-aminopyridine resulted in similar changes to what was observed with the addition of pyridine and further validates the use of cyclic voltammetry to assess the coordination of pyridine.…”
Section: Resultsmentioning
confidence: 65%
“…1), however, cobaloximes still continue to generate a lot of interest due to their high activity towards electrocatalytic proton reduction. 15,19,3739 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13] Thea dvantages of cobaloximes are their facile synthesis and the tunability of their catalytic properties by modifying the substituents on the equatorial and/or axial ligands. [13][14][15][16] Moreover,t hey exhibit high proton-reduction activity at ar elatively low overpotential [17] and can operate in aqueous solutions [18,19] even under aerobic conditions. [20,21] Recently,v ersatile strategies were reported for their immobilization onto metal-oxide [13,22] and carbon-based [23][24][25] surfaces for applications in electro-and photoelectrocatalytic H 2 production.…”
mentioning
confidence: 99%
“…TheG C/ MWCNT-PyCo electrodes displayed areversible redox wave at E 1/2 = 0.24 Vv ersus the standard hydrogen electrode (SHE), whereas ar eversible process was observed at E 1/2 = 0.08 Vv ersus SHE with GC/MWCNT-pPyCo.T hese redox processes are attributed to the cobaloximes reversible Co III / Co II redox couple. [16] Thes mall shift in redox potential between the monomer and polymer is presumably due to achange in the chemical environment surrounding the cobalt center upon incorporation into ap olymer chain. Thes mall redox waves observed in the case of GC/MWCNT-PyCo at E red = 0.13 Vand E ox = 0.08 Vm ay be the result of different adsorption interactions of the PyCo generating varying chemical environments on the GC/MWCNT surface.I n contrast, the single redox process observed with GC/ MWCNT-pPyCo results most likely from amore homogenous environment around the cobalt catalysts,p rovided by the polymeric matrix.…”
mentioning
confidence: 99%